Religious literary literacy in pesantren: a phenomenological study of moral and spiritual learning - Lamri Lamri; Else Liliani; Sri Harti Widyastuti (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study explores how santri (student) in pesantren (Islamic boarding school) education experience and interpret religious literary practices as a medium for moral and spiritual learning and conceptualizes these experiences into a religious literary literacy (RLL) model. Using a qualitative interpretative phenomenological approach through interpretative phenomenological analysis (IPA), the study examines santri’s lived experiences and meaning-making processes. Data were generated through in-depth semi-structured interviews with eight santri from four pesantren in East Java and Yogyakarta, Indonesia, supported by analysis of student literary works and pesantren literacy archives. The analysis involved iterative stages of close reading, coding, thematization, and hermeneutic interpretation. The findings reveal three interconnected dimensions of RLL: i) literature as spiritual and moral reflection; ii) transformative selfhood and moral consciousness developed through reflective reading and writing; and iii) pesantren as a pedagogical ecosystem integrating faith, ethics, and creative expression. These dimensions form the RLL model, which conceptualizes literary practice as a cyclical process of devotion, reflection, and self-transformation. The study contributes theoretically by extending the concept of religious literacy beyond textual competence toward experiential and interpretative moral formation. Practically, the model offers a conceptual framework for designing reflective literacy programs in Islamic education that support character development and address contemporary moral challenges among youth.